Local Community Participation in Ecotourism Development: A Qualitative Analysis in the Binh-Tri-Thien Region, Vietnam - Le, Toai Anh. Autor; Butowski, Leszek. Autor; Quirini-Popławski, Łukasz. Autor; Nguyen, Son Hoang. Autor (IGiPZ PAN, 2025)
Ecotourism is a sustainable tourism form that emphasizes the harmonious relationship between human and nature, with local communities playing a key role in providing services and protecting natural resources. Using semi-structured interviews conducted at various ecotourism sites in the Binh-Tri-Thien region (Central Vietnam), this study has illuminated the role of local communities in fostering ecotourism development. Communities actively contribute by offering distinctive services and products while preserving cultural values, safeguarding the environment, and fostering sustainable relationships with visitors. The findings reveal that local communities play key roles as tour guides, providers of accommodation services, and producers of handicrafts, generating income and promoting cultural exchange. However, barriers such as skill deficiencies and gender inequalities continue to limit the participation of certain groups, particularly women. While cultural and environmental preservation is given considerable attention, the risk of traditional cultural erosion remains significant, especially among ethnic minority communities. Based on these insights, the study recommends expanding the scope of research and integrating qualitative and quantitative methods to enhance the reliability of findings.
24 cm
Keywords: Geografia -- czasopisma [KABA]; Polska -- geografia -- czasopisma [KABA]